PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MENGGUNAKAN GEOGEBRA CLASSROOM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF ADA TOPIK SSEGIEMPAT DAN SEGITIGA KELAS VII SMP - Wenny Kurnia (Jurnal Edukasi dan Penelitian Matematika, 2022)
This study aims to determine the characteristics of LKPD using Geogebra Classroom which is valid, practical, and effective in improving students' creative thinking skills. This LKPD uses the Plomp development model which consists of 3 stages, namely the preliminary research stage, the prototype stage, and the assessment stage. The subjects of this study were 9 grade VII students of SMP N 4 Bathin Solapan. The instruments used are validation sheets, questionnaires for teachers and students, and questions about creative thinking skills. In this study, valid, practical, and effective LKPD were obtained. The LKPD is valid with a result of 88.19% in the very valid category. The results of the educator's response questionnaire obtained a practicality value of 93.33% with a very practical category. Meanwhile, for the student questionnaire, the practicality value of 84.44% was obtained in the very practical category. The LKPD was categorized as quite effective with an average score of 46.87% in the pre-test and 66.67% in the post-test.. Keywords– LKPD, Geogebra Classroom, Valid, Practical, Effective